Pengembangan Media Pembelajaran Scrapbook Berbasis Budaya Palembang Pada Topik Bangun Datar - Widyasari, Nurbaiti; Permata Putri, Adella Kirsa (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2019)
This study is to develop a learning media whole package that includes material to two-dimensional figures with Palembang-based culture. This research uses research and development (R&D). The subjects in this study were students of class II, III, IV SD Negeri 3 Margo Bhakti. Analysis of the data used is qualitative descriptive with a percentage. Development of instructional media scrapbook Palembang culture based on topics two-dimensional figure with phase ADDIE. The results showed that the assessment included 1) validation of material experts got 71.61% with valid criteria, 2) validation of linguists got 87.5% with very valid criteria, 3) validation of media experts got 88.57% with very valid criteria. Assessing students' responses 1) small group trials get an average of 11.16 with high criteria, 2) large group trials get an average of 11.06 with high criteria. Based on the above assessment, the learning media scrapbook Palembang culture-based on the topic of the two-dimensional figure is valid or appropriate to use as a medium of learning mathematics on the topic of a two-dimensional figures.